(untitled) (Revista Contexto & Saúde, 2025)
The SARS-CoV-2 virus, the etiological agent of coronavirus disease 2019 (COVID-19), infects host cells and begins its viral replication process. After the viral incubation period, the disease can lead to symptoms that range from flu-like symptoms to severe forms of disease (such as respiratory failure), posing a risk to life. The exacerbated inflammatory response in COVID-19 is associated with changes in leukocyte (global and differential counts), platelet, and C-reactive protein (CRP) levels, which when evaluated in isolation have lower power to provide an accurate clinical picture. However, blood count ratios such as lymphocyte-to-total leukocyte ratio (L/WBC) and platelet-to-lymphocyte ratio (PLR) can assertively infer the immuno-inflammatory clinical status. The objective of this study was to evaluate whether leukocyte parameters can be used as biomarkers of prognosis and outcome in critically ill COVID-19 patients. A total of 236 patients admitted to the COVID-19 ICU in a medium-sized and highly complex hospital located in the northwest of the state of Rio Grande do Sul were included in the study. The clinical and laboratory parameters evaluated were CRP, L/WBC and PLR, collected at patient admission and outcome. Data were expressed as mean and standard deviation and analyzed using the Student’s T test, considering a significance level of 5%. We identified the applicability of PCR, L/WBC and PLR as predictive biomarkers in critically ill COVID-19 patients. Serum concentrations of CRP, L/WBC and PLR can predict the outcome and indicate the prognosis of COVID-19 patients with COVID-19.